Gamification in Education: Enhancing Engagement and Motivation in Uzbekistan's High Schools (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Thanks to the internet and the growing trend of content consumption, students increasingly lack the patience and time for activities that require extended focus. This is particularly problematic for subjects like history, which demand sustained engagement with reading materials. The shift away from deep focus poses challenges for students and educators alike, especially in fostering critical thinking and comprehension skills. This paper aims to discuss the possibility to use the concept of gamification in the educational system of Uzbekistan with reference to the mentioned difficulties. Point systems associated with ‘bribes’, badges and leaders or ‘trophy’ systems have been used in the past because they promote interest and healthy competition among students. However, besides using the above benefits which show that the program changes engagement and motivates students, it also brings about some issues especially among those who do not like competition or have low performance. This paper shows how game based approach enhances concentration and fun in learning while at the same time ensuring that the methods are not overused to a level of stressing students who learn at a slower pace, by also incorporating traditional teaching methods for learning. The studies indicate that, if correctly utilised, gamification increases motivation and the learning achievements in addition to emphasising the cooperative component. This research is useful as it develops an approach to using gamification in the cultural and educational context of Uzbekistan and supports the use of both big and small applications based on a variety of students’ needs.